A New Proposed Public Key Cryptography Based on Bio Strands - AL-Wattar, Auday (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The recent rapid advancement of technology has increased the capability of attackers. The main challenge to information security is the requirement for using unconventional philosophies and alternative means and focusing on new aspects to achieve security. This article proposes a new method that uses the collected genetic information on GenBank and its characteristics. The statistics that were calculated for the data that were hidden using this method prove that they meet the security standards. This paper employs unique elements for achieving information hiding based on that information.